TADVIDYASAMBHASHA BUDDHIVARDHANANAM - Kumar, Raju; Pandey, Vijay Shankar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the sequential line of human evolution, development and civilization, the human beings are always fallowed a specific pattern of meet to each other for the proper understandings and hence, learning and functioning, which ultimately made them educated and wiser formerly. These meetings, specific to get more educated or learning skills are called as Tadvidyasambhasha to which Acharya Charak explained as foremost among all which indulges in enhancement in human thinking or so, called understanding about the life things. This study represents analytical of extents of enhancement in intelligence through interactive or intellectual means of Tadvidyasambhasha against the most indicated mind governing drug, called as Medhya Rasayana Shankhapushpi. Individuals involved are grouped in two groups group-I and group-II having a strength of 30 in each group, are nominated for their grouped analysis by making grouped data charts for a minimum of 60 days study.